Factors Affecting Teacher Competencies in Schools Huai Mek District Under the Kalasin Primary Educational Service Area Office 2 Kalasin Province - Harnlumpang , Sittiporn; Yupass , Yupaporn; Kosonkittiumporn, Saovalak (Interdisciplinary Academic and Research Journal, 2023)
Teacher competency is very important in developing and promoting student learning at all levels. To achieve effective learning and create better academic results. The objectives of this research were 1) to study teacher competency. 2) To study factors affecting the competency of teachers. And 3) to study the recommendations on factors affecting the competency of teachers. The population is teachers in educational institutions in Huai Mek District Under the Office of Kalasin Primary Educational Service Area Office 2, Kalasin Province, total number of 271 people. The sample group was 165 people using Taro Yamane's formula and simple random sampling. The research tools were questionnaires. Statistics used in data analysis were percentage, mean, frequency, and standard deviation. and multiple regression analysis. The research findings were as follows: (1) the teacher competency as the overall level was at a high level. (2) Factors affecting the competency of teachers were; the nature of work performed, teacher's attitude, and social support together predicted 33.60% with a statistical significance at the .05 level. And (3) a suggestion on factors affecting the competency of teachers where; knowledge and skills should be developed Teachers should develop their knowledge and skills in the content they teach. Must research and improve teaching content with modern educational concepts and guidelines. should develop teaching skills Teachers should develop practical teaching skills. This includes lesson planning. Use of appropriate teaching tools and techniques to create a learning atmosphere that encourages creativity and happy learning Assessment skills should be developed. Teachers should be skilled in systematically and individually evaluating student learning. Learning management skills should be developed. Teachers should have the skills to create and manage learning activities that are consistent with the concept of competency development in terms of knowledge, skills, minds, and ethics. Teachers should have good communication skills in communicating with students, parents, and other educational colleagues. Lifelong learning skills should be developed. Teachers should encourage and support students to develop the learning skills necessary for adaptation and lifelong learning preparation.